2006
DOI: 10.1007/s10482-006-9078-6
|View full text |Cite
|
Sign up to set email alerts
|

Conditions required for citrate utilization during growth of Lactobacillus casei ATCC334 in chemically defined medium and Cheddar Cheese extract

Abstract: Conditions required for citrate utilization by Lactobacillus casei ATCC334 were identified. Citrate was utilized by this microorganism in modified Chemically Defined Media (mCDM) as an energy source, solely in the presence of limiting concentrations of galactose. The presence of glucose inhibited citrate utilization by this microorganism even when added in limiting concentrations. Utilization of citrate occurred at pH 6.0 +/- 0.2 and 5.1 +/- 0.2. Together these observations suggest that citrate is an energy so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Thomas (1987) showed that citrate was utilised in Cheddar cheese with various added Lactobacillus plantarum strains. Recently, Dı´az-Mun˜iz and Steele (2006), demonstrated that Lb. casei ATCC334 was capable of degrading citrate in Cheddar cheese extract.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas (1987) showed that citrate was utilised in Cheddar cheese with various added Lactobacillus plantarum strains. Recently, Dı´az-Mun˜iz and Steele (2006), demonstrated that Lb. casei ATCC334 was capable of degrading citrate in Cheddar cheese extract.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, L. rhamnosus H2, which was able to utilize citrate in culture media, consumed citrate at the slowest rate in cheese and was unable to deplete the citrate present in the cheeses for the duration of the 90 d of ripening. The effect of environmental conditions on citrate utilization of L. casei ATCC334 was demonstrated by Díaz-Muñ iz and Steele (2006), who found that citrate was utilized only when the galactose concentration was limiting in culture media, whereas when Cheddar cheese extract was used as the culture medium, citrate was utilized regardless of the galactose concentration. In the same study, the presence of 2% sodium chloride in chemically defined culture media restricted the growth and affected citrate utilization by this strain.…”
mentioning
confidence: 99%
“…Conversely, cheese extract with a 4.5% salt-in-moisture content was not found to be inhibitory for citrate catabolism. Studies investigating the influence of pH, monoand divalent cations, and carbohydrate type and concentration on citrate utilization of nonstarter lactic acid bacteria have reported contradictory observations, often resulting from the changes in experimental design and environmental conditions (Palles et al, 1998;Díaz-Muñ iz and Steele, 2006 strain dependent and strongly influenced by the environmental conditions.…”
mentioning
confidence: 99%
“…However, the strain was able to grow in tryptone-based medium deprived of carbohydrate sources, indicating that the strain has the ability to adapt to starvation. Several researchers have attempted experimental approaches to simulate the conditions similar to those found in ripening cheese using chemically defined media or cheese extract to understand growth characteristics and physiology of NSLAB (Adamberg et al, 2006;Díaz-Muñ iz & Steele, 2006;Gummalla & Broadbent, 2001;Kieronczyk, Skeie, Olsen, & Langsrud, 2001). The conditions in cheese are more complex and stressful for bacterial cells due to multiple factors impacting on growth, survival and metabolism simultaneously.…”
Section: Effect Of Inoculum Size On Growth and Lactose Utilizationmentioning
confidence: 99%
“…However, these experimental conditions do not represent the relatively stressful environments encountered in the cheese matrix, conditions that could significantly influence the survival and metabolism of members of the microflora. A few recent investigations focused on the use of starvation and/or energylimited conditions simulating the depletion of lactose concentration during cheese ripening (Adamberg, Adamberg, Laht, Ardö , & Paalme, 2006;Díaz-Muñ iz & Steele, 2006;Rouch & Britz, 2004).…”
Section: Introductionmentioning
confidence: 99%